Pendapatan Usahatani Cabai Merah Berdasarkan Musim di Provinsi Jawa Tengah - Muhammad Royun Nuha; Tursina Andita Putri; Anisa Dwi Utami (Institut Pertanian Bogor, 2023)
The difference in seasonality in the red chili farming business affects the allocation of the use of production factors and the availability of its supply in the market, which is suspected to affect the cost structure and revenue of the farming business. This study aims to calculate the cost structure, revenue, and earnings of red chili farming businesses in the dry and wet seasons in Central Java Province. Data was collected from the 2013 Agricultural Census: 2014 Horticultural Crop Business Household Survey and a 2535 red chili farmers sample. The methods used include the analysis on income, cost and revenue structure, revenue, R/C ratio, and Mann-Whitney differential test. The results showed that the cash and overall costs of farming red chili in the dry season were higher than in the wet season. So are the total and cash revenues. Farming in the dry season is more profitable in terms of cash income, net farm income, R/C ratio, return to total capital, and return to land, which is higher than in the wet season. The results of the Mann-Whitney difference test showed a significant difference in the income factors and R/C ratio of the red chili farm business in the two seasons. Keywords: cost structure, income, R/C ratio, red chili, season